Desconsideração da personalidade jurídica no novo Código de Processo Civil - Vieira, Tábata Dias Fagundes (2017)
This paper aims to show that the institute of legal personality benefits business relations because it amortizes the inherent risks of business activity, separating the patrimony of the company from that belonging to the shareholders. Although the Civil Code enumerates several private entities with legal personality, this study will deal exclusively with legal personality linked to the business activity, that is, the companies and the individual company with limited liability. In order to protect against abuses of legal personality, the possibility of disregarding legal personality arises. In this context, the lack of adequate procedural regulation allowed the violation of due process, and the new of Civil Procedure Code seeks to ensure the adversarial principle, and full defense to the legal personality affected. The focus of the new Civil Procedure Code is to maintain the protection of those who contract with the legal personality, without undue damage to the partners' individual patrimony. With the correct procedural means to apply the disregard of the legal personality, the civil procedural law made a great progress towards the procedural effectiveness